2008
DOI: 10.1677/jme-08-0087
|View full text |Cite
|
Sign up to set email alerts
|

A RAS recruitment screen identifies ZKSCAN4 as a glucocorticoid receptor-interacting protein

Abstract: To search for proteins interacting with the glucocorticoid receptor, we adapted Aronheim's reverse RAS recruitment system relying on the Saccharomyces cerevisiae mutant cdc25-2, which has a temperature-dependent defect in its RAS signaling pathway driving proliferation. The full-length human glucocorticoid receptor (NR3C1, isoform-a) was attached to the yeast plasma membrane in either of two orientations and used as bait to screen a HeLa cell cDNA library. Library proteins were fused to constitutively active, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
(47 reference statements)
0
13
0
Order By: Relevance
“…The ZKSCAN4 protein is mainly localized in the nucleus and highly expressed in the brain. Ecker et al found that ZKSCAN4 is a glucocorticoid receptor-interacting protein and co-precipitated with the glucocorticoid receptor when both proteins were overexpressed in HEK293 cells (Ecker et al, 2009). 3.3.2.2. Genetic association.…”
Section: Zkscan4mentioning
confidence: 99%
“…The ZKSCAN4 protein is mainly localized in the nucleus and highly expressed in the brain. Ecker et al found that ZKSCAN4 is a glucocorticoid receptor-interacting protein and co-precipitated with the glucocorticoid receptor when both proteins were overexpressed in HEK293 cells (Ecker et al, 2009). 3.3.2.2. Genetic association.…”
Section: Zkscan4mentioning
confidence: 99%
“…This might be explained by defects in neuronal connectivity, as well as by reduced oxytocin neurons in the hypothalamus, because mutant mothers are deficient in milk ejection. 94 SCAN domain transcription factors are able to interact with proteins as diverse as the von Hippel-Lindau tumor suppressor protein, which is a component of an E3 ubiquitin ligase (ZnF197), 92 the E3 ubiquitin ligase Siah1a (Pw1/Peg3), 95 the neurotrophin receptor p75 (NRIF), 96 peroxisome-proliferator-activated receptors (SDP1 and PGC-2), 97 the glucocorticoid receptor (Znf307), 98 the transcriptional repressor Jumonij/Jarid2 (Zfp496), 99 the NSD1 histone lysine methyltransferase (Nizp1), 100 and the tumour necrosis factor mediator TRAF2 (Pw1/Peg3). 101 Several SCAN domain proteins are involved in the control of cell survival and proliferation.…”
Section: The Scan Domain Familymentioning
confidence: 99%
“…It is GC resistant, due to qualitatively and quantitatively defective GR expression [30], but has been transfected with a functional GR thereby restoring GC sensitivity [26]. Jurkat GR cells [26] were stably transfected with a lentiviral construct (pHR-MMTV-VNP) enabling GC-dependent expression of a fl uorescent reporter gene [27] and subjected to limiting dilution cloning. For this, cells were plated in 96-well plates at densities of 25, 5 or 1 cell per well.…”
Section: Generation Of Jurkat Gr -Mmtv-vnpmentioning
confidence: 99%
“…Th is GBA, based on the measurement of GR-dependent reporter gene activity, can be employed to measure GC bioactivity from small amounts of serum or other biologic fl uids. A human T-cell leukemia derived cell line (Jurkat), stably transfected with a plasmid expressing the GR [26] and a fl uorescent reporter gene under control of the mouse mammary tumor virus (MMTV) LTR promoter [27], was used to establish the assay. Th us, Venus nuclear fl uorescent protein (VNP), with about 10-fold higher fl uorescence intensity than green fl uorescent protein (GFP) [28], has been brought under control of the liganded GR and was used as the assay's reporter.…”
mentioning
confidence: 99%